THE URGENCY OF MORAL VALUES IN THE FORMATION OF INTELLECTUAL CHARACTER - Galela, Afrizal (Abjadia : International Journal of Education, 2024)
The formation of intellectual character in education plays a crucial role in producing individuals who are intellectually intelligent and possess high moral integrity. This article outlines the urgency of integrating moral values into the educational process to achieve this goal. Through literature review and theoretical analysis, the article highlights the role of moral values in shaping strong and positive character, as well as the impact of integrating moral values with intellectual learning. The findings show that schools that emphasize moral values are able to develop holistic and balanced character in students. The integration of moral values with intellectual learning through a holistic curriculum is key to creating individuals who are not only academically intelligent but also morally noble. This article also discusses the challenges in integrating moral values and intellectual character, as well as the efforts required from schools, families, and communities to overcome these challenges. Thus, the integration of moral values and intellectual character is an important step in shaping well-rounded, intelligent, and moral individuals to face future challenges effectively.